Comparative study of the application fish apartments in Situbondo and Probolinggo, East Java, Indonesia - WAHYU ISRONI; ZULKISAM PRAMUDIA; ANJAS SASANA BAHRI; MEGA ASRI RISQIANA; NURUL MAULIDA; TIA DWI IRAWANDANI (Society for Indonesian Biodiversity, 2023)
Abstract. Isroni W, Pramudia Z, Bahri AS, Risqiana MA, Maulida N, Irawandani TD. 2023. Comparative study of the application fish apartments in Situbondo and Probolinggo, East Java, Indonesia. Biodiversitas 24: 4034-4045. Fisheries resources which are common property in their utilization are vulnerable to overfishing conditions due to exploratory actions. In addition, the use of destructive fishing gear and habitat degradation has a great impact on fisheries productivity which continues to decrease. Fish apartments as alternative artificial habitat have been successfully applied in Probolinggo, especially for coral organisms. This study compares the application of fish apartments in two different locations, Karang Katon Probolinggo and Karang Mayit Beach Situbondo. Through descriptive and valuative approaches, the survey results showed that in Karang Katon there were 5 species, the highest composition level is Acanthurus achilles (51.56%).Karang Mayit Beach there were 3 species, the highest composition level is Chaetodon octofasciatus (60.56%). The highest abundance is Acanthurus achilles (34.4 ind/m2) in Karang Katon and Chaetodon octofasciatus (42.2 ind/m2) in Karang Mayit Beach. The diversity index in Karang Katon-1.280, while in Karang Mayit Beach-0.853. The dominance index in Karang Katon 0.343, while in Karang Mayit Beach 0.496. Based on this research, the analysis showed positive results for both different locations, indicating it can be used as new habitats for sustainability and increased productivity of fisheries resources.